Real-world implementation of the 2020 KDIGO guidelines for diabetes management in chronic kidney disease: a single-center retrospective study - Levin-Iaina, Nomy; El’Nasasra, Hatem; Reiner-Benaim, Anat (Frontiers in Nephrology, 2025)
BackgroundType 2 diabetes mellitus (T2DM) is an increasing global pandemic, frequently complicated by diabetic kidney disease, that may result in end stage kidney disease and increased cardiovascular morbidity and mortality. The 2020 KDIGO guidelines recommend SGLT2 inhibitors and GLP1RAs for cardio-renal protection in patients with T2DM and kidney disease. This study aimed to evaluate the implementation of the 2020 KDIGO guidelines among adult diabetic patients receiving nephrology care.Material and methodsThis retrospective study included 587 patients with T2DM and chronic kidney disease treated in a single nephrology clinic between 1 May 2021 and 31 May 2022. Demographic, diabetes related, and CKD-related data was assessed. The utilization of the 2020 KDIGO recommended medications was analyzed during the study period, along with factors influencing treatment decisions.ResultsThe findings revealed a low initial utilization of recommended medications, with only 12.9% and 10.4% of patients treated with SGLT2i and GLP1RA, respectively. Only a modest, but significant, increase in SGLT2i usage was observed by the end of the study period. Factors associated with underutilization of SGLT2i and GLP1RA included older age and decreased kidney function. The study also highlights a significant gap between the recommendations given by nephrologists during the study period and the actual use of recommended medications in the last clinic visit.ConclusionsIn conclusion, the study provides insights into the challenges of implementing KDIGO guidelines in real-world nephrology clinical setting. Further research is needed to explore the reasons behind low adherence to guidelines and strategies to improve compliance, ultimately enhancing patient outcomes in the management of kidney disease in T2DM.